Die leierskap van die Jerusalem-kerk as weldoeners tydens die ontmoeting met Paulus: Galasiers 2:10 en antieke Joodse resiprositeit - Joubert, Stephan (HTS teologiese studies, 2001)
The leadership of the Jerusalem church as benefactors at the meeting with Paul: Galatians 2:10 and ancient Jewish reciprocity. From the perspective of Jewish reciprocity, the leadership of the Jerusalem church bestowed an important beneit on Paul at their meeting in the year 48 by recognising the contents of his gospel. This benefit placed Paul under the obligation to respond with a suitable beneit of his own as proof of his gratitude. The Jerusalem leadership indicated what an adequate response to their beneit would entail: a caritative undertaking to help solve the plight of the poor in their midst. In the same vein as Seneca in De Beneficiis, Paid now presents himself in Galatians 2:10 as the "ideal beneiciary" within this reciprocal relationship with Jerusalem. He knows how to show his gratitude in public and how to repay his debts to his benefactors.